Use of Trichoderma species as a growth promoter in mint and basil plants - Chagas, Lillian França Borges; Chagas Junior, Aloisio Freitas; de Castro, Henrique Guilhon (Seven Editora, 2023)
The use of microorganisms in medicinal plants may provide an increase in biomass. The objective of this work was to evaluate Trichoderma as a plant growth promoter, for the capacity of phosphate solubilization and synthesize of indole acetic acid (IAA) in vitro, and biomass production of two medicinal plants, basil and mint. Cultures were inoculated with two species of Trichoderma. The crop biomass as well as the relative efficiency were determined. Trichoderma species that solubilized phosphate and produced IAA, provided significant results in the accumulation of biomass of the crops, with relative efficiency of 276% for mint and 141% for basil, in relation to the control. The Trichoderma isolates showed phosphate solubilization capacity and IAA synthesis. Therefore, the studied crops presented biomass increase. These strains verified their capacity as plant growth promoters. DOI: https://doi.org/10.56238/colleinternhealthscienv1-090